High‐resolution variable‐density 3D cones coronary MRA. Issue 3 (14th July 2015) - Addy, Nii Okai; Ingle, R. Reeve; Wu, Holden H.; Hu, Bob S.; Nishimura, Dwight G.
<x xml:space="preserve">Abstract</x> Purpose To improve the spatial/temporal resolution of whole‐heart coronary MR angiography by developing a variable‐density (VD) 3D cones acquisition suitable for image reconstruction with parallel imaging and compressed sensing techniques. Methods A VD 3D cones trajectory design incorporates both radial and spiral trajectory undersampling techniques to achieve higher resolution. This design is used to generate a VD 3D cones trajectory with 0.8 mm/66 ms isotropic spatial/temporal resolution, using a similar number of readouts as our previous fully sampled cones trajectory (1.2 mm/100 ms). Scans of volunteers and patients are performed to evaluate the performance of the VD trajectory, using non‐Cartesian L1‐ESPIRiT for high‐resolution image reconstruction. Results With gridding reconstruction, the high‐resolution scans experience an expected drop in signal‐to‐noise and contrast‐to‐noise ratios, but with L1‐ESPIRiT, the apparent noise is substantially reduced. Compared with 1.2 mm images, in each volunteer, the L1‐ESPIRiT 0.8 mm images exhibit higher vessel sharpness values in the right and left anterior descending arteries. Conclusion Coronary MR angiography with isotropic submillimeter spatial resolution and high temporal resolution can be performed with VD 3D cones to improve the depiction of coronary arteries. Magn Reson Med 74:614–621, 2015. © 2015 Wiley Periodicals, Inc.